LIQUID HOLDUP IN TURBULENT CONTACT ABSORBER - Haq, A.; Zaman, M.; Inayat, M. H.; Chughtai, I. R. (The Nucleus, 2020)
Dynamic liquid holdup in a turbulent contact absorber was obtained through quick shut off valves technique. Experiments were carried out in a Perspex column. Effects of liquid velocity, gas velocity, packing diameter packing density and packing height on dynamic liquid holdup were studied. Hollow spherical high density polyethylene (HDPE) balls were used as inert fluidized packing. Experiments were performed at practical range of liquid and gas velocities. Holdup was calculated on the basis of static bed height. Liquid holdup increases with increasing both liquid and gas velocities both for type 1 and type2 modes of fluidization. . Liquid holdup increases with packing density. No effect of dia was observed on liquid holdup.